Позднеплейстоценовый северный олень Поднепровья - Белан, Н.Г. (Вестник зоологии, 1983)
Late Pleistocene reindeer remnants of the Dnieper area described as com- pared with materials from other localities in the Ukraine. The reindeer of the Ukraine belongs to Rangifer tarandus guettardi (Desmarest, 1822): facial part of the cranium short, diasteme short, teeth large, lower jaw body high and incrassate, female horns thin and ovoid, extremity joints wide, metapodia of medium length. Suggested habitat: grassland with thin snow cover.